DETERMINAN INFORMASI ASIMETRIS PADA INDEKS SAHAM LQ45 - Ni Nyoman Ayu Diantini (University of Merdeka Malang, 2015)
Managers directly involved in the management of companies often have internal company information moreabout the companys future prospects than shareholders. This asymmetric information that occurs between theinvestor and the manager will affect their decisions on investment and capital structure. The purpose of thisstudy was to analyze the effect of firm size, research and development expenditure, growth opportunities andthe number of shareholders of the asymmetric information on LQ45 index in the Indonesia Stock Exchange.The samples in this study was conducted with a purposive sampling on a consistent company that listed inLQ45 index between 2011-2013, total samples are 25 companies. The analysis technique used multiple linearregression analysis. The key findings of the paper are firm size has a significant negative effect on asymmetricinformation and number of shareholders have significant positive effect on asymmetric information. VariableR D expenditure and growth opportunities showed no significant effect on asymmetric information.